KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA PADA PEMBELAJARAN MODEL RME - Kase, Seni K.; Daniel, Farida; Taneo, Prida N. L. (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2023)
This research aimed to produce a study of students' mathematical concept understanding abilities in classes with Realistic Mathematics Education (RME) model learning and classes that did not receive RME model learning. This research was a quantitative method of quasi experiment model designed in the form of non-equivalent control group design involving two research classes determined using purposive sampling technique. The instrument used was a test of students' mathematical concept understanding ability in the form of description questions. The data analysis technique in this study used an independent sample t-test and N-gain score. The results of the analysis showed that students' mathematical concept understanding ability in the class that received RME model learning was better than that of those who did not receive RME model learning. The increase in students' mathematical concept understanding ability in the class with RME model learning was in a low category with an average gain score of 0.025. The low increase is due to the limited learning time at school during the adaptation period of new habits, so that learning with the RME model does not run effectively.